2020
DOI: 10.1177/1756286420954083
|View full text |Cite
|
Sign up to set email alerts
|

Standardized algorithm for muscle selection and dosing of botulinum toxin for Parkinson tremor using kinematic analysis

Abstract: Background: Inadequate efficacy and significant side effect profile makes pharmacological treatment of Parkinson’s disease (PD) tremor challenging. Personalized dosing of botulinum toxin type A (BoNT-A) using tremor analysis has shown efficacy and safety for treating upper limb tremor. This study incorporated a novel, standardized treatment algorithm for determining injection pattern and BoNT-A dosing, customizable by the physician, in PD patients with disabling tremor in one or both arms. Methods: This open-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…It was concluded that the use of a personalized strategy for bilateral injections provided effective tremor control in patients with ET and could eliminate the variability underlying clinical evaluation and accelerate the regain of arm function. Similar strategy was employed in another recent study to evaluate the effectiveness and safety of BoNT-A in 47 PD participants who received 4 serial BoNT-A treatments with follow-ups at 6 weeks post-treatment over 42 weeks [23]. There was significant improvement in tremor amplitude and UPDRS tremor score (p < -.05) with improvement in the QoL.…”
Section: Study Classmentioning
confidence: 85%
“…It was concluded that the use of a personalized strategy for bilateral injections provided effective tremor control in patients with ET and could eliminate the variability underlying clinical evaluation and accelerate the regain of arm function. Similar strategy was employed in another recent study to evaluate the effectiveness and safety of BoNT-A in 47 PD participants who received 4 serial BoNT-A treatments with follow-ups at 6 weeks post-treatment over 42 weeks [23]. There was significant improvement in tremor amplitude and UPDRS tremor score (p < -.05) with improvement in the QoL.…”
Section: Study Classmentioning
confidence: 85%
“…Kinematics detected a significant reduction in PD tremor amplitudes by 70% over the treatment course. In an open study the same study group found a significant improvement of tremor amplitude in 41.6%, and improved quality of life in 23%, with efficacy in 45% of participants [ 46 ].…”
Section: Non-licensed Indicationsmentioning
confidence: 99%
“…Clinical consequence: At present, the injection of BoNT cannot be recommended for treatment of tremors in PD. We have to await the results of studies that are presently being conducted, but in individual cases, injection may well be worth taking into consideration The possibility of a functional paresis is a limiting factor [ 51 ], thus making a personalized approach advisable [ 46 ].…”
Section: Non-licensed Indicationsmentioning
confidence: 99%
“…Needle-guided techniques (e.g., electromyography [EMG], electrical stimulation), ultrasound, or surface EMG and anatomy are used for more accurate targeting of muscles contributing to tremor motion. Using such techniques aid the injector to select muscles for injection, which has improved functional outcomes and minimized excessive arm weakness [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, there is no available software for tremor analysis to customize BoNT-A dosing for the selection of muscle groups without substantial clinical judgment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these limiting aspects may reduce feasibility for use in real-world clinics and consistency in replicating a standardized approach of BoNT-A injection pattern determination [ 6 ]. Newer comprehensive technology-based injection techniques, such as the Yale method (EMG needle-probing of forearm muscles) [ 10 , 11 ] and whole-arm kinematic tremor assessments by Jog et al [ 12 , 13 , 14 , 15 ] can now guide clinical customization of BoNT-A dose and muscle selections based on each patient’s tremor characteristics [ 19 ]. Both BoNT-A dosing techniques have similarly demonstrated significant tremor reduction, improved motor function, and quality of life while significantly reducing the incidence of muscle weakness in tremulous ET and PD patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%